The Effect of Budget Participation and Budget Feedback on School Quality High School/Vocational in Medan City - Wardani Pulungan, Rafika; Situmeang, Chandra; Ishak, Muhammad (International Journal of Social Science, Education, Communication and Economics, 2024)
The problem in this study is the relatively low Quality of Private Senior High Schools/Vocational High Schools in Medan City. Many factors can affect the quality of a school, including budget participation and budget feedback. This study aims to test the effect of Budget Participation and Budget Feedback on the Quality of Private Senior High Schools/Vocational High Schools (SMA/SMK) in Medan City. The population of this study was all Private Senior High Schools/Vocational High Schools in Medan City totaling 405 schools, of which 157 were Private Vocational High Schools and 248 were Private High Schools. The research sample was 35 schools using the Simple Random Sampling Method, with a quantitative research type. The data used are primary and secondary data. Primary data were obtained through direct distribution of questionnaires to respondents (research subjects), while secondary data were obtained from https://bansm.kemdikbud.go.id/. The independent variables used are Budget Participation (PA) and Budget Feedback (UA). The dependent variable used is School Quality (KS). This study uses multiple linear regression analysis techniques using the SPSS statistical test tool. Based on the results of partial and simultaneous tests, this study shows that Budget Participation and Budget Feedback have a significant effect on School Quality. This is evidenced by partial testing (t-test) of Budget Participation of 0.026 or less than 0.05, and Budget Feedback of 0.035 or less than 0.05. Then, the simultaneous significance value (F test) of 0.045 or less than 0.05. The conclusion of this study shows that the effect of budget participation and budget feedback on school quality shows significant results.